(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To analyze the rare clinical case of uveal melanoma in a 4 у/о child. Material and methods: Management of a 4 y/o child with uveal melanoma, Results: Melanoma of the ciliary body with spreading into the iris, anterior chamber angle and suspicion of intrascleral growth was diagnosed after complete clinical examination. According to the conclusion of the international consilium enucleation of the eyeball was performed. Pathomorphology diagnosis: ciliary body and iris melanoma of the mixed cellular type. Drainage zone blocks by melanin seeds. No external scleral layers and extrabulbar invasion. Conclusions: The presented clinical case suggests the possibility of uveal melanoma developing in young children. Pediatric ophthalmologists have to be more attentive to the pigmented lesions and don’t exclude the melanoma occurrence in children’s age.